THE ARTIST’S BOOK AS A GENRE IN CONTEMPORARY VISUAL ART – DEFINITION AND MAIN TYPES OF ARTISTS’ PUBLICATIONS - Regina Dalkalacheva (Издател)
The article lays the theoretical foundations for considering and understanding the Artist's Book as a unique form of expression in contemporary art. The Artist’s Book is defined as a free visual work of the artist that is conceived and realized through the specific expressive means of the book and is realized independently of the traditional structures and distribution network of formal book publishing. Essential characteristics define the Artist’s Book not as a literary genre but as a genre in the visual arts that derives from innovative ideas of the late 19th century and revolutionary currents in the avant-garde in the 20th century. The text elucidates the historical genesis and articulates the conceptual and aesthetic features of the two main movements: Artists’ Books realized in limited editions and conceptual Artists’ Books, also called Artists’ Publications. The current trends in the highly dynamic development of contemporary Artists’ Books, which are defined by a diversity of forms and innovative plastic and pictorial approaches of artists, are commented.